Outcome of Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Treatment practice and outcome of generalized convulsive status epilepticus (GC-SE) in The Netherlands were studied at the Dr Hans Berger Clinic, Breda and University Hospital, Nijmegen, The Netherlands.